KEPEMIMPINAN SEKOLAH PADA NEW NORMAL DAPAT MENINGKATKAN MUTU PENDIDIKAN - elva zuleni; Riri Marfilinda (Jurnal Riset Pendidikan Dasar Dan Karakter, 2021)
This study examines how the ideal principal leadership in the new normal is to improve the quality of education. The existence of Covid-19 is a factor that accelerates humans to make changes. From the literature study conducted, it can be concluded that in conditions of massive change, leaders are needed to respond quickly, agile and deftly to respond to situations appropriately. So transformational leadership competence is needed in the new normal situation. This change is referred to by many as the educational revolution. Therefore, it is imperative that the principal with all his potential and his surroundings must collaborate to bring the best education for students in improving the quality of education. Keywords: Leadership, new Normal and quality